DIDACTIC PRINCIPLES FOR TEACHING NATURAL SCIENCES FROM THE USE OF SCIENTIFIC SKILLS - Elizabeth Rodríguez (LÍNEA IMAGINARIA, 2025)
The teaching of natural sciences from the use of scientific competencies represents a pedagogical approach that goes beyond the mere transmission of knowledge. This model focuses on developing practical and cognitive skills that allow students to not only understand scientific concepts, but also apply them in real contexts. Given this, this essay is framed in the objective of analyzing the didactic principles for teaching natural sciences from the use of scientific competencies. Integrating scientific competencies in the teaching of natural sciences allows for a deeper connection with the environment and the daily reality of students. By addressing relevant and current topics, teachers can contextualize learning, making scientific concepts more accessible and understandable. This approach also encourages a critical and reflective mindset, as students learn to question, investigate, and seek solutions to specific problems. Ultimately, focusing on the development of scientific competencies helps create informed and responsible citizens who can actively participate in society and make informed decisions about scientific and environmental issues.